2016
DOI: 10.1371/journal.pone.0152310
|View full text |Cite|
|
Sign up to set email alerts
|

Temporal Patterns of Influenza A and B in Tropical and Temperate Countries: What Are the Lessons for Influenza Vaccination?

Abstract: IntroductionDetermining the optimal time to vaccinate is important for influenza vaccination programmes. Here, we assessed the temporal characteristics of influenza epidemics in the Northern and Southern hemispheres and in the tropics, and discuss their implications for vaccination programmes.MethodsThis was a retrospective analysis of surveillance data between 2000 and 2014 from the Global Influenza B Study database. The seasonal peak of influenza was defined as the week with the most reported cases (overall,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
76
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 27 publications
(30 reference statements)
9
76
0
Order By: Relevance
“…However, this relative incidence pattern can vary across different regions of the world,52 although our finding is comparable to results from France, where influenza B peaked an average of 3.8 weeks later than influenza A 53…”
Section: Discussionsupporting
confidence: 73%
“…However, this relative incidence pattern can vary across different regions of the world,52 although our finding is comparable to results from France, where influenza B peaked an average of 3.8 weeks later than influenza A 53…”
Section: Discussionsupporting
confidence: 73%
“…In the tropics, seasons are not that well marked resulting in a less predictable seasonal dynamics. There are reports of semi-annual or year-round influenza activity [8, 9]. Studies of influenza in the tropics started recently.…”
Section: Introductionmentioning
confidence: 99%
“…These data agree with the data of Nascimento‐Carvalho et al who found a predominance of influenza during the rainy, summer, and fall seasons, in the city of Salvador, Brazil. On the other hand, Caini et al demonstrated that influenza cases peaked between June and September (dry season), in countries of the Southern hemisphere, including south and southeast Brazil. Regarding the seasonality of RSV, Bouzas et al analyzed the incidence of RSV associated with seasonal distribution in the city of Salvador, Brazil.…”
Section: Discussionmentioning
confidence: 99%